Intermolecular and Intramolecular Association of Poly(ethylene glycol) Mediated by Sodium Dodecyl Sulfate in Dilute Solutions - Chen, Xiaoming; Ren, Lin (Asian Journal of Chemistry, 2012)
In mixed solutions of poly(ethylene glycol) and sodium dodecyl sulphate the aggregation of surfactants with polymer chains strengthens the intermolecular or/and intramolecular hydrophobic junctions, resulting in the intermolecular or/and intramolecular association of poly(ethylene glycol) mediated by sodium dodecyl sulphate. If the polymer concentration c > 0.017 g/mL different polymer chains associate together through intermolecular hydrophobic junctions. The reduced viscosity of poly(ethylene glycol) increases as the concentration of sodium dodecyl sulphate increases. On the other hand, if c < 0.017 g/mL, the poly(ethylene glycol) chains are almost separated and the intramolecular association of poly(ethylene glycol) through intramolecular hydrophobic junctions dominates. Therefore the reduced viscosity of poly(ethylene glycol) decreases considerably as the concentration of sodium dodecyl sulphate increases.